Feasibility of Distorted Born Iterative Method for Detecting Early Stage of Heart Failure - Akıncı, Mehmet Nuri; Bilgin, Egemen; Joof, Sulayman; Doğu, Semih (IEEE, 2020)
In this paper, we analyze the feasibility of using microwaves to detect early stage of congestive heart failure, which causes water accumulation in the lungs. To this aim, a slice from realistic human torso phantom, which consists of all human tissues and organs, is considered. Constitutive parameters of the phantom are calculated by multiple order Cole-Cole model at operating frequency. Then, the scattered field is calculated via method of moment and a 30 dB additive white Gaussian noise is added to create a more realistic scenario. In the solution of inverse scattering phase, distorted Born iterative method is utilized. The presented results show the feasibility of the proposed method.
Keywords: Congestive heart failure; Pulmonary edema detection; Microwave imaging; Distorted born iterative method